Delayed Deglaciation by Downwasting of the Northeast Avalon Peninsula, Newfoundland: An Application of the Early Postglacial Pollen Record - Brown MacPherson, Joyce (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1996)
ABSTRACTBasal radiocarbon dates from lake sites indicate that final degiaciation began at most a few centuries before 10 ka BP on the interior plateau and proceeded by down-wasting. Comparison of the pollen record with the sequence of vegetation from the Storbreen glacier foreland, Norway, studied by the Jotunheimen Research Expeditions, indicates that pioneer herb and dwarf shrub stages gave way within 200 years to shrub-birch heath into which spruce migrated at about 8.5 ka BP. It is shown that double maxima of dwarf shrubs result from the existence of terrains of different ages within each catchment at the time when lake sediment accumulation began. An independently dated pollen record from St. John's Harbour confirms the timing and mode of degiaciation and demonstrates that the Avalon Peninsula ice cap did not extend beyond the present coast at the beginning of the Holocene. The delays in both degiaciation and the immigration of spruce are attributed to cold ocean temperatures associated with eastward discharge of meltwater from the Laurentide Ice Sheet.